Landscape Sacralisation in Post-communist Poland. (2nd January 2017) - Przybylska, Lucyna; Czepczyński, Mariusz
ABSTRACT: Landscape sacralisation is the process of filling the cultural landscape with religious phenomena and giving it a sacred character with elements of ritualised devotion. This paper examines this process in Poland during and since the communist era (1945–1989), and with a particular emphasis on late communist and post-communist times (1980–2013). It is argued that faith, politics, economy and religious 'traditions of place' are the most important factors shaping landscape sacralisation in Poland, particularly since 1980. Three types of landscape sacralisation are identified – architectural, linguistic and seasonal – and this paper discusses recent trends in these processes of landscape sacralisation with respect to their prevailing religious and non-religious dimensions. In recent decades, the Polish landscape has been filled with diverse religious objects and forms (churches, crosses, monuments, public processions, annual festivals and rural and urban nomenclature) associated chiefly with the Roman Catholic Church, the dominant denomination in the country. It is argued that scholarly appreciation of landscape sacralisation is a vital means of identifying the religiosity of Polish people during and since the communist era.